Pengaruh Substitusi Tepung Labu Kuning (Cucurbita Moschata) Terhadap Kadar Β-Karoten Dan Daya Terima Produk Flakes - Febriani, Rima; , Pramudya Kurnia, STP, MAgr (2016)
Deficiency of vitamin A is one of the four main nutrient problems in Indonesian that must be solved. As many as three millions of childrean are blind due to the deficiency of vitamin A. In the toddlers, the deficiency will succeptible to infections diseases, such as diarhea, pneumona and finally death. Pumpkin flour can be used as substitute material in making flakes. The purpose of the research was to determine the effect of pumpkin flour substitution on β-carotene and acceptance levels of flakes. The research was conducted by subtituting the pumpkin flour at various levels, were 0%, 10%, 20% and 30%. The results indicated that β-carotene of all treatment of flakes was below 62,9 mg/kg. The highest acceptance of flakes was given by 0% substitution, followed by 20%. Keywords: flakes, food acceptance, beta carotene, yellow pumpkin.